Clinical vitamin D levels are associated with insular volume and inferior temporal gyrus white matter surface area in community-dwelling individuals with knee pain - Strath, Larissa J.; Hernandez, Pedro Valdes; Nodarse, Chavier Laffitte; Johnson, Alisa J.; Edberg, Jeffrey D.; Fillingim, Roger B.; Cruz-Almeida, Yenisel (Frontiers in Neuroscience, 2022)
Context Vitamin D is an essential, fat soluble micronutrient long-known for its effects on calcium homeostasis and bone health. With advances in technology, it is being discovered that Vitamin D exerts its effects beyond the musculoskeletal system. Vitamin D has since been noted in nervous system health and functioning, and is becoming a target of interest in brain health, aging, and chronic pain outcomes. Objectives We and others have previously shown that deficient Vitamin D status is associated with greater pain severity across a variety of conditions, however the reason as to why this relationship exists is still being understood. Here, we sought to examine associations between Vitamin D status and brain structure in those with chronic knee pain. Methods Structural MRI imaging techniques and whole brain analyses were employed and serum Vitamin D were collected on 140 participants with chronic pain. Covariates included age, sex, race and site, as these data were collected at two separate institutions. ANOVAs using the clinical cut points for Vitamin D status (deficient, insufficient, and optimal) as well as continuous regression-based Vitamin D effects were employed to observe differences in brain volume. P-value was set to 0.017 after correction for multiple comparisons. Results We discovered that individuals in our sample (age = 50+; 63.6% female; 52.1% Non-Hispanic Black) who were either clinically deficient (<20 ng/mL) or insufficient (20–30 ng/mL) in serum Vitamin D had significant differences in the gray matter of the left circular insular cortex, left inferior temporal gyrus, right middle temporal gyrus, as well as decreased white matter surface area in the right inferior temporal gyrus compared to those considered to have optimal levels (>30 ng/mL) of serum Vitamin D. Conclusion Evidence from these data suggests that Vitamin D, or lack thereof, may be associated with pain outcomes by mediating changes in regions of the brain known to process and interpret pain. More research understanding this phenomenon as well as the effects of Vitamin D supplementation is warranted.